2019
DOI: 10.1055/s-0039-1693693
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet PI3K Modulates Innate Leukocyte Extravasation during Acid-Induced Acute Lung Inflammation

Abstract: Introduction Blood platelets are increasingly recognized as modulators of leukocyte effector functions in various pathologies including acute lung injury (ALI). ALI is a life-threatening disease, caused by damage to the alveolar epi- and endothelium. Excessive accumulation of leukocytes leads to severe lung inflammation, resulting in impaired lung function and hypoxemia. Objective Since leukocyte migration is modulated by activated platelets and phosphatidylinositol 3-kinase (PI3K) signaling is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Interestingly, in TPO ASO treated mice levels of Ly6C hi monocytes and macrophages were significantly reduced in the lung consistent with previous reports that platelets are essential for the recruitment of monocytes to sites of inflammation, 41,42 and necessary for effective inflammation resolution 43 . Of significance, in our model of lower airway dysbiosis, we found that platelet depletion by either TPO ASO treatment of anti‐CD42b resulted in the same impairment to monocyte and macrophage recruitment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, in TPO ASO treated mice levels of Ly6C hi monocytes and macrophages were significantly reduced in the lung consistent with previous reports that platelets are essential for the recruitment of monocytes to sites of inflammation, 41,42 and necessary for effective inflammation resolution 43 . Of significance, in our model of lower airway dysbiosis, we found that platelet depletion by either TPO ASO treatment of anti‐CD42b resulted in the same impairment to monocyte and macrophage recruitment.…”
Section: Discussionsupporting
confidence: 91%
“…28,38 Following pulmonary inflammation, platelets are detected coupled to leukocytes in bronchoalveolar lavage fluid 39 and have been found to migrate into the extravascular compartment of the lung during allergen-induced airway inflammation. 40 Profiling of whole lung homogenates found that Cd41 mRNA was significantly reduced in TPO ASO-treated mice; for the recruitment of monocytes to sites of inflammation, 41,42 and necessary for effective inflammation resolution. 43 Of significance, in our model of lower airway dysbiosis, we found that platelet depletion by either TPO ASO treatment of anti-CD42b resulted in the same impairment to monocyte and macrophage recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation caused by inappropriate neutrophil activation will result in serious damage to the host tissues. Consequently, functional conversion of neutrophils is regulated by numerous mechanisms (35)(36)(37). In recent years, there have been an increasing number of studies showing that neutrophil surface receptors play specific roles in the pathogenesis of some diseases and can affect its functions via various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that VWF-GPIbα signaling through PI3K and Akt was responsible for platelet integrin activation (Spater et al, 2018;Kral-Pointner et al, 2019). Thus, PI3K/Akt signaling might be involved in VWF-induced platelet P-selectin translocation because that P-selectin translocation was one of a series of platelet activation's landmark events, such as platelet morphology changes, integrin activation, particle release (Pselectin translocation, etc.…”
Section: Vwf-mediated P-selectin Translocation Was Pi3k and Akt Dependent For Platelet Under Flowsmentioning
confidence: 99%
“…It is demonstrated that inhibiting VWF-GPIbα interaction can reduce effectively the force-induced platelet P-selectin translocation (Goto et al, 2000;Rahman and Hlady, 2021), while VWF-GPIbα signaling through PI3K/Akt participated in platelet integrin activation and high shear stress-induced platelet P-selectin translocation (Spater et al, 2018;Chen et al, 2019;Kral-Pointner et al, 2019). It is believed that catch-slip bond transition governs the interaction of VWF with GPIbα and retains but shifts the shear stress threshold in the cases of type 2B or 2M VWF mutations that result in bleeding disorders (Coburn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%